COMMON COUPLED FIXED POINTS FOR TWO PAIRS OF w -COMPATIBLE MAPS IN PARTIAL G -METRIC SPACES - Rao, K.P.R.; Kishore, G.N.V.; Sadik, S.K. (Kathmandu University Journal of Science Engineering and Technology, 2016)
In this paper we prove a unique common coupled fixed point theorem for two pairs of w-compatible mappings satisfying two contractive conditions in partial G-metric spaces. We also furnish an example to support our main theorem.